Analysis of Factors Affecting the Availability of Medication at UPT Puskesmas for BPJS Patients - Andriana Saragih, Mona; Samran; Rahmad Gurusinga (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The availability of medicines at UPT Puskesmas Silalahi for BPJS patients is influenced by drug procurement, pharmacy management, and BPJS policies. Although the BPJS e-catalogue system aims to improve efficiency, the mismatch between supply and patient needs remains a major issue, affecting the quality of healthcare services at the Puskesmas. Research Objective: This study aims to analyze the factors affecting the availability of medicines at Puskesmas Silalahi and to find solutions to improve the existing drug procurement system. Research Method: This research uses a descriptive qualitative approach with interviews, observations, and documentation. The research informants consist of Puskesmas management, BPJS officers, and the head of pharmacy. Research Results: The results indicate that drug procurement at Puskesmas Silalahi is hindered by delayed BPJS payments, discrepancies between the e-catalogue medicines and actual needs, and limited budgets. These factors affect the smooth delivery of healthcare services and the availability of medicines. Conclusion: More efficient drug procurement management, increased budgets, and better coordination between BPJS and drug suppliers are necessary to ensure timely availability of medicines for BPJS patients at Puskesmas Silalahi.